Periarteriolar localization of mast cells promotes oriented interstitial migration of leukocytes in the hamster cheek pouch. - Raud, J. (1989)
As studied by intravital microscopy, mast cell-dependent inflammatory reactions evoked by antigen or compound 48/80 in the hamster cheek pouch involved leakage of plasma and emigration of leukocytes exclusively from the venules. The leukocyte diapedesis and subsequent tissue migration induced by antigen or compound 48/80 were oriented from the venules towards adjacent arterioles. In contrast, leukocyte emigration induced by a mast cell-independent stimulus, leukotriene B4, did not show preferential orientation towards arterioles. Moreover, mast cells were abundant in the hamster cheek pouch, and they were localized predominantly along arterioles, rather than along venules. Because mast cells are considered to be the source of the chemotactic mediators causing the leukocyte emigration, the periarteriolar mast cell localization may be of functional significance by creating chemotactic gradients between arterioles and venules, thereby promoting oriented and effective interstitial migration of leukocytes. Whether or not a similar mechanism is operative in other species and tissues remains to be established, however, arteriolar predominance of mast cells was observed also in rat calvarial periosteum and in mouse skin.